Eficácia do método pilates no tratamento da dor lombar crônica não específica - Miyamoto, Gisela Cristiane (2011)
The primary aim of this master thesis was to evaluate the efficacy of the Pilates approach in patients with chronic non-specific low back pain. The specific aims were: 1) to systematically review using a meta-analysis approach the current evidence of the Pilates exercises in patients with chronic non-specific low back pain; and 2) to investigate the effectiveness of the addition of a modified Pilates approach to a minimal intervention in patients with chronic non-specific low back pain. Low back pain is an important health and socio-economic problem, which is associated with high costs, disability and absenteeism worldwide. The treatment effects of chronic low back pain recommended by clinical practice guidelines are, on average, moderate. Therefore, it is necessary to further investigate interventions that are likely to be effective for this condition. Exercise therapy is considered an excellent option in the treatment of chronic low back pain, being the specific stabilization exercises such as the Pilates approach one of these possibilities. However, there is little high quality evidence on the efficacy of the Pilates approach in patients with chronic non-specific low back pain. The first trials on this topic were published from 2006. This topic was reviewed by some authors and at this point there are six clinical trials aiming to test the effects of Pilates’ exercises in patients with chronic non-specific low back pain. However, the current published systematic reviews did not include these trials. Therefore it would be necessary to systematically review all these trials in order to summarize the evidence of this treatment approach in patients with chronic non-specific low back pain. Chapter two presents the results of a systematic review using a meta-analysis approach that included five randomized controlled trials. A total of five studies analysed pain intensity as an outcome, being one study compared Pilates against the McKenzie, three studies compared Pilates against minimal interventions and one trial compared three Pilates regimes. Only two studies analysed disability as an outcome, comparing Pilates against minimal interventions. The methodological quality of these studies ranged from two to eight points in a zero to 10 quality scale, being only one study having high methodological quality. This review showed that Pilates was not better than the Mackenzie method or minimal interventions considering pain, however Pilates was better than minimal interventions considering disability (mean difference = 4.9 points; 95% CI 4.0 to 5.8 points). Chapter three describes a protocol of a randomized, assessor blinded, controlled trial. This study included 86 chronic non-specific low back pain patients that were randomly assigned into two treatment arms: an education group, which received an educational booklet, and the Pilates group which received the educational booklet and a modified Pilates treatment approach. The outcomes assessed were: pain intensity, general and specific disability, global perceived effect and kinesiophobia; these outcomes were assessed at baseline, six weeks and six months after randomization. Treatment expectation and credibility were also assessed at baseline and after the first session of treatment, respectively. This study started in October 2010 and is now concluded. Chapter four presents the results of this study which objective was to investigate the effectiveness of the addition of a modified Pilates approach to a minimal intervention in patients with chronic non-specific low back pain. Improvements in pain intensity (mean difference = 2.2 points; 95% CI 1.1 to 3.2), general disability (mean difference = 2.7 points; 95% CI 1.0 to 4.4) and global perceived effect (mean difference = -1.5 points; 95% CI -2.6 to -0.4) at short term were observed in favour to the Pilates method. No differences were observed for any outcomes at 6 months follow up. We concluded that the addition of a modified Pilates method is beneficial when compared to a minimal education intervention at short term, however this effects were not sustained for the 6 months follow up. All studies presented in this thesis are important due to their contribution in testing the efficacy of the Pilates approach in the treatment of chronic low back pain. Firstly, previous studies on the Pilates method have low methodological quality and their results should be interpreted cautiously. Moreover, it is suggested that Pilates is better than a minimal intervention in terms of disability, but not for pain intensity. Secondly, Pilates’ exercises should be considered in the treatment of patients with chronic low back pain in terms of pain intensity, disability and global perceived effect in a short term. More high-quality trials on this topic should be performed in order to test the effects of this intervention in patients with chronic non-specific low back pain.